Agrolandscapes and their role in ensuring environmental safety - Larysa Piskunova; Tetiana Zubok; Alla Klepko; Kateryna Кarabach; Alina Kudryavytska (Наукові горизонти)
The purpose of the study was to analyse in depth the role of agrolandscapes in ensuring environmental safety and to investigate their impact on the environment, with a special emphasis on aspects of biodiversity, soil protection, and water management. The study covered a wide range of activities, including the collection and systematisation of scientific materials, a comparative analysis of different management approaches, and the development of a theoretical model of environmental safety that allows assessing the effectiveness of existing practices. The main results of the study indicated that agrolandscapes characterised by a high level of integration of natural elements and agricultural components can provide a significantly higher level of biodiversity compared to less integrated counterparts. In particular, forest and forest-steppe agrolandscapes have proven to be the most effective in conserving species, which is critical for maintaining ecological balance. However, steppe and dry steppe landscapes require urgent and comprehensive measures to improve the state of biodiversity, as their ecological sustainability is under threat. Thus, the results of the study emphasised the need to introduce innovative approaches to agrolandscape management that can contribute to the conservation of natural resources and improve environmental safety. The developed theoretical model revealed that the most sustainable agrolandscapes are those where natural ecosystems are harmoniously combined with agricultural land. The results confirmed the hypothesis that effective management of agrolandscapes contributes to improving environmental safety and reducing negative environmental impacts, in particular, by controlling erosion and managing water resources. The conclusions emphasised the need to implement agroforestry, support environmental approaches in policies and a system of monitoring the state of agrolandscapes for the sustainable development of agricultural regions, which would facilitate adaptation to the challenges of climate change